Proceedings / XI. International Conference on Logistics in Agriculture 2017, 9. November 2017, Novo mesto, Slovenia - Marina Bajić; Lisec, Andrej (2017)
11th International Conference of Logistics in Agriculture is a traditional conference in the field of logistics, which is very important in agriculture. The conference is organized by the Municipality of Sevnica, Grm Novo mesto – Centre of Biotechnics and Tourism, University of Maribor, Faculty of Logistics and Landscape Governance College. This year the topic of the conference is Short supply chain in Logistics in Agriculture. Our conference proceedings have several papers on different topics which are especially dealing with the distribution of locally produced food. This is one of the most important things for improving the tourism in the region. A part of this year’s conference is also a Round table on Challenges of plastics in agriculture.
Keywords: agriculture; logistics; locally produced food; waste; packaging